Negative electrode material and battery

By doping N and P elements into the negative electrode material of lithium-ion batteries, controlling the spherical degree and orientation degree, combined with amorphous carbon, the problems of expansion stress and lithium ion transmission efficiency of the negative electrode material during charging and discharging are solved, and high Preference capacity, excellent cycle stability and fast charging performance with low expansion rate.

CN119315020APending Publication Date: 2025-01-14BTR NEW MATERIAL GRP CO LTD

Patent Information

Application Number
CN202411850109.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-16
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

During the charging and discharging process, existing lithium-ion battery negative electrode materials are prone to cause large local expansion stress, particle rupture, affecting the transmission efficiency of lithium ions, making it difficult to meet the fast charging requirements, and the cycle capacity retention rate and first-time Coulomb efficiency decline.

Method used

By doping N and P elements in the negative electrode material, and controlling the spherical shape of the particles to 0.75≤S10≤0.85, 0.85≤S50≤0.9, 0.9≤S90≤1.0, combining amorphous carbon as a binder, the spherical shape of the particles is enhanced. degree and orientation reduce internal resistance and promote the transmission and deintercalation efficiency of lithium ions.

Benefits of technology

It improves the specific capacity, cycle stability and fast charging performance of the negative electrode material, reduces the expansion rate and internal resistance, extends the cycle life of the battery, and meets the performance requirements of fast charging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119315020A_ABST
    Figure CN119315020A_ABST
Patent Text Reader

Abstract

The invention provides a negative electrode material and a battery, the negative electrode material comprises secondary particles, the secondary particles comprise primary particles and amorphous carbon connected with the primary particles, and the primary particles comprise graphite; the negative electrode material comprises at least one of an N element and a P element; in the negative electrode material, the corresponding particle sphericity degree is S10 when the cumulative volume distribution percentage reaches 10%, the corresponding particle sphericity degree is S50 when the cumulative volume distribution percentage reaches 50%, the corresponding particle sphericity degree is S90 when the cumulative volume distribution percentage reaches 90%, S10 is larger than or equal to 0.75 and smaller than or equal to 0.85, S50 is larger than or equal to 0.85 and smaller than or equal to 0.9, and S90 is larger than or equal to 0.9 and smaller than or equal to 1.0. The negative electrode material provided by the invention is relatively good in particle sphericity degree, the isotropy of the negative electrode material can be improved, and the specific capacity and the fast charge rate performance of the negative electrode material can be improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of negative electrode materials, and in particular, to negative electrode materials and batteries. Background Art

[0002] The rapid development of lithium-ion batteries has brought about rapid changes in human life. As one of the core components of lithium-ion batteries, negative electrode materials have a significant impact on the electrochemical properties of lithium-ion batteries. Therefore, the development of cost-effective negative electrode materials is of great significance in lithium-ion battery research. Graphite is widely used as a negative electrode material for lithium-ion batteries due to its stable structure and high theoretical specific capacity (372mAh / g). In order to improve the fast charging performance of negative electrode materials and reduce the expansion of negative electrode materials during the cycle, the graphite material particles are generally subjected to secondary granulation.

[0003] However, the current negative electrode material particles are irregular, which can easily lead to large local expansion stress during the charge and discharge process, which in turn causes particle rupture and intensifies the side reaction with the electrolyte. In addition, the irregular negative electrode material particles will affect the transmission efficiency of lithium ions, making it difficult for graphite negative electrode materials to meet fast charging requirements, and the cycle capacity retention rate and first coulomb efficiency of the negative electrode material will decrease. Summary of the invention

[0004] The present application provides a negative electrode material and a battery. The negative electrode material can meet the fast charging requirements, and the negative electrode material has high specific capacity, first coulombic efficiency and cycle stability.

[0005] In a first aspect, the present application provides a negative electrode material, the negative electrode material comprising secondary particles, the secondary particles comprising primary particles and amorphous carbon connecting the primary particles, the primary particles comprising graphite; the negative electrode material comprising at least one of N element and P element; In the negative electrode material, when the cumulative volume distribution percentage reaches 10%, the corresponding particle sphericity is S 10 When the cumulative volume distribution percentage reaches 50%, the corresponding particle sphericity is S 50 When the cumulative volume distribution percentage reaches 90%, the corresponding particle sphericity is S 90 , 0.75≤S 10 ≤0.85, 0.85≤S 50 ≤0.9, 0.9≤S 90 ≤1.0.

[0006] In some embodiments, the sphericity index of the negative electrode material is R ≥ 1.05, R = S 50 / S 50’, wherein 2g of negative electrode material was dispersed in a mixed solution of 45mL of water and 5mL of ethanol, and after ultrasonic crushing at a frequency of 20kHz for 10min, the particle sphericity corresponding to the cumulative volume distribution percentage of the negative electrode material reaching 50% was S 50’ .

[0007] In some embodiments, the negative electrode material includes at least one of N element and P element.

[0008] In some embodiments, the mass percentage of N element in the negative electrode material is 0.5%~2%.

[0009] In some embodiments, the mass percentage of P element in the negative electrode material is 0.05%~0.5%.

[0010] In some embodiments, the graphite includes at least one of artificial graphite and natural graphite.

[0011] In some embodiments, the graphite includes spherical natural graphite.

[0012] In some embodiments, the average particle size of the primary particles is 1 μm to 5 μm.

[0013] In some embodiments, the repose angle of the negative electrode material is 30° to 50°.

[0014] In some embodiments, the orientation degree OI of the negative electrode material is 1-5.

[0015] In some embodiments, the compaction density of the negative electrode material at 5T pressure is 1.5 g / cm 3 ~1.9 g / cm 3 .

[0016] In some embodiments, the tap density of the negative electrode material is 0.5 g / cm 3 ~0.9g / cm 3 .

[0017] In some embodiments, the specific surface area of ​​the negative electrode material is 2 m 2 / g~10 m 2 / g.

[0018] In some embodiments, the median particle size of the negative electrode material is 10 μm to 30 μm.

[0019] The present application provides a battery, which includes the above-mentioned negative electrode material.

[0020] The technical solution of this application has at least the following beneficial effects: The negative electrode material provided in the present application contains at least one of the N element and the P element; these elements have a strong binding force with lithium ions, can promote the desolvation of lithium ions in the electrolyte, reduce the interfacial impedance of the solid-liquid interface of the negative electrode material, is beneficial to the transmission of lithium ions, and improves the specific capacity of the negative electrode material; when the particle sphericity of the negative electrode material is low, during the compaction of the electrode sheet, the negative electrode material is more inclined to have the long axis parallel to the direction of the collector, the electrode sheet orientation of the negative electrode material is large, the transmission path of the lithium ions becomes longer, and the low particle sphericity will lead to inconsistent lithium ion deintercalation rates in different directions, and the internal resistance of the negative electrode material increases, which is not conducive to the improvement of fast charging performance. The present application can improve the transmission efficiency of lithium ions by controlling the negative electrode material to contain at least one of the N element and the P element, and at the same time control the particle sphericity of the negative electrode material to satisfy 0.75≤S 10 ≤0.85, 0.85≤S 50 ≤0.9, 0.9≤S 90 ≤1.0. Due to the high sphericity of the negative electrode material and the high degree of isotropy of the negative electrode material, the orientation of the pole piece prepared by the negative electrode material is smaller, and the lithium ion deintercalation rate is closer, which can reduce the internal resistance of the negative electrode material, and the lithium ion transmission channels are more and shorter, which is beneficial to improving the fast charging performance of the battery. Controlling the sphericity of the particles while doping N and P elements can not only ensure the lithium ion transmission efficiency of the surface of the particles, but also make the lithium ion deintercalation rate close to each other, synergistically improve the lithium ion deintercalation rate and transmission efficiency, so that the negative electrode material can meet the fast charging performance. In addition, during the cycle of the battery, the negative electrode material shrinks and expands radially. Due to the high degree of isotropy, the expansion stress can be effectively released, which is beneficial to maintain the stability of the negative electrode material structure, reduce particle breakage, and reduce the intensification of the side reaction between the negative electrode material and the electrolyte caused by the collapse of the particle structure, which is beneficial to improve the cycle performance of the negative electrode material and reduce expansion. Therefore, the negative electrode material provided in the present application improves the sphericity of the secondary particles of the negative electrode material while doping N element and / or P element, so that the negative electrode material has high specific capacity, excellent cycle stability, and low expansion rate, and can meet the fast charging performance of the negative electrode material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0022] Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application.

[0023] Figure 2This is a graph of the sphericity test data of the negative electrode material prepared in Example 1 of the present application. DETAILED DESCRIPTION

[0024] In order to better illustrate the present application and facilitate understanding of the technical solution of the present application, the present application is further described in detail below. However, the following embodiments are only simple examples of the present application and do not represent or limit the scope of protection of the present application. The scope of protection of the present application shall be subject to the claims.

[0025] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0026] The present application provides a negative electrode material, the negative electrode material comprising secondary particles, the secondary particles comprising primary particles and amorphous carbon connecting the primary particles, the primary particles comprising graphite; the negative electrode material comprising at least one of N element and P element; The particle sphericity S corresponding to the cumulative volume distribution percentage in the negative electrode material reaches 10% 10 is 0.75 to 0.85; the particle sphericity S corresponding to the cumulative volume distribution percentage of the negative electrode material reaches 50% 50 =0.85~0.90; the particle sphericity S corresponding to the cumulative volume distribution percentage of the negative electrode material reaches 90% 90 =0.90~0.1.

[0027] The negative electrode material provided in the present application contains at least one of the N element and the P element; these elements have a strong binding force with lithium ions, can promote the desolvation of lithium ions in the electrolyte, reduce the interfacial impedance of the solid-liquid interface of the negative electrode material, is beneficial to the transmission of lithium ions, and improves the specific capacity of the negative electrode material; when the particle sphericity of the negative electrode material is low, during the compaction of the electrode sheet, the negative electrode material is more inclined to have the long axis parallel to the direction of the collector, the electrode sheet orientation of the negative electrode material is large, the transmission path of the lithium ions becomes longer, and the low particle sphericity will lead to inconsistent lithium ion deintercalation rates in different directions, and the internal resistance of the negative electrode material increases, which is not conducive to the improvement of fast charging performance. The present application can improve the transmission efficiency of lithium ions by controlling the negative electrode material to contain at least one of the N element and the P element, and at the same time control the particle sphericity of the negative electrode material to satisfy 0.75≤S 10 ≤0.85, 0.85≤S 50 ≤0.9, 0.9≤S 90≤1.0. Due to the high sphericity of the negative electrode material and the high degree of isotropy of the negative electrode material, the orientation of the pole piece prepared by the negative electrode material is smaller, and the lithium ion deintercalation rate is closer, which can reduce the internal resistance of the negative electrode material, and the lithium ion transmission channels are more and shorter, which is beneficial to improving the fast charging performance of the battery. Controlling the sphericity of the particles while doping N and P elements can not only ensure the lithium ion transmission efficiency of the surface of the particles, but also make the lithium ion deintercalation rate close to each other, synergistically improve the lithium ion deintercalation rate and transmission efficiency, so that the negative electrode material can meet the fast charging performance. In addition, during the cycle of the battery, the negative electrode material shrinks and expands radially. Due to the high degree of isotropy, the expansion stress can be effectively released, which is beneficial to maintain the stability of the negative electrode material structure, reduce particle breakage, and reduce the intensification of the side reaction between the negative electrode material and the electrolyte caused by the collapse of the particle structure, which is beneficial to improve the cycle performance of the negative electrode material and reduce expansion. Therefore, the negative electrode material provided in the present application improves the sphericity of the secondary particles of the negative electrode material while doping N element and / or P element, so that the negative electrode material has high specific capacity, excellent cycle stability, and low expansion rate, and can meet the fast charging performance of the negative electrode material.

[0028] In some embodiments, the particle sphericity S corresponding to the cumulative volume distribution percentage reaching 10% is 10 Specifically, it can be 0.75, 0.78, 0.8, 0.82, 0.83 or 0.85, etc., and is not limited here.

[0029] In some embodiments, the particle sphericity S corresponding to the cumulative volume distribution percentage reaching 50% is 50 Specifically, it can be 0.85, 0.86, 0.87, 0.88, 0.89 or 0.9, etc., and is not limited here.

[0030] In some embodiments, the particle sphericity S corresponding to the cumulative volume distribution percentage reaching 90% is 90 Specifically, it can be 0.9, 0.91, 0.92, 0.95, 0.96, 0.97, 0.98 or 1.0, etc., and is not limited here.

[0031] In some embodiments, the sphericity index of the negative electrode material is R ≥ 1.05, R = S 50 / S 50’ , wherein 2g of negative electrode material was dispersed in a mixed solution of 45mL of water and 5mL of ethanol, and after ultrasonic crushing at a frequency of 20kHz for 10min, the particle sphericity corresponding to the cumulative volume distribution percentage of the negative electrode material reaching 50% was S 50’ It should be noted that after ultrasonic pulverization, some particles will break and pulverize into primary particles. 50’It can indicate the sphericity of primary particles in negative electrode materials. When the R value is too small, S 50 With S 50’ The difference is small, only the particle size becomes larger, which shows that the orientation of the secondary particles obtained by secondary granulation has not been effectively improved. When the R value is too large, it means that the sphericity of the primary particles is low. Even through secondary granulation, it is still difficult to improve the sphericity of the secondary particles, and the isotropy of the secondary particles decreases. Preferably, 1.05≤R<1.15.

[0032] The sphericity index R of the negative electrode material is controlled within the above range, and the sphericity of the secondary particles is higher than that of the primary particles, that is, the sphericity of the secondary particles formed by the agglomeration and connection of multiple primary particles is higher, because part of the amorphous carbon repairs or makes up for the granulation defects of some secondary particles, so that the sphericity of the secondary particles is further improved. When the sphericity of the primary particles is too low, the sphericity of the secondary particles is difficult to improve, and the isotropy of the secondary particles decreases. Therefore, the present application controls the sphericity of the primary particles and the sphericity of the second particles within a suitable ratio range, which can make the sphericity of the negative electrode material higher, the orientation of the negative electrode material is low, and the negative electrode material is in the cycle process. Due to the continuous embedding and extraction of lithium ions between the graphite layers, the expansion stress generated can be released in multiple directions, reducing the particle breakage caused by excessive local expansion stress of the negative electrode material particles, improving the expansion effect of the negative electrode material, and effectively improving the cycle performance of the negative electrode material.

[0033] In some embodiments, the secondary particles include primary particles and amorphous carbon, that is, the amorphous carbon acts as a binder to connect the primary particles, which can improve the electron transfer efficiency of the negative electrode material.

[0034] In some embodiments, at least a portion of the surface of the secondary particles has amorphous carbon. An appropriate amount of amorphous carbon can reduce direct contact between the electrolyte and graphite, thereby reducing the occurrence of side reactions.

[0035] In some embodiments, the amorphous carbon may be formed by carbonizing at least one of polyvinyl pyrrolidone, polyacrylamide, polyvinyl alcohol, and hydroxymethyl cellulose.

[0036] In some embodiments, the primary particles include a core graphite and a carbonaceous coating layer located on the surface of the core graphite, wherein the carbonaceous coating layer includes amorphous carbon.

[0037] In some embodiments, the mass percentage of the N element in the negative electrode material is 0.5% to 2%, specifically 0.5%, 0.6%, 0.8%, 0.9%, 1%, 1.2%, 1.5%, 1.6%, 1.8% or 2%, etc., and of course, it can also be other values ​​within the above range, which are not limited here. The nitrogen element doped in the negative electrode material can provide more active lithium storage sites. When the nitrogen content in the negative electrode material is too little, the improvement on the capacity of the negative electrode material is limited. When the nitrogen element is doped too much, the pore volume of the negative electrode material will also increase synchronously, the specific surface area of ​​the negative electrode material will also increase, the side reaction between the negative electrode material and the electrolyte will intensify, and the first coulombic efficiency of the negative electrode material will decrease. The present application controls the mass percentage of the N element in the negative electrode material within the above range, which is beneficial to increase the capacity of the negative electrode material and improve the cycle retention rate of the negative electrode material.

[0038] In some embodiments, the mass percentage of the P element in the negative electrode material is 0.05% to 0.5%, specifically 0.05%, 0.08%, 0.1%, 0.15%, 0.2%, 0.25%, 0.3%, 0.35%, 0.4% or 0.5%, etc., and of course, it can also be other values ​​within the above range, which is not limited here. When the mass percentage of the P element in the negative electrode material is too much, the phosphorus atoms in the negative electrode material are easily dissolved, resulting in partial decomposition of the electrolyte, especially in high temperature environments, resulting in a decrease in the cycle capacity of the negative electrode material. When the mass percentage of the P element in the negative electrode material is too little, the capacity improvement of the negative electrode material is limited. The present application controls the mass percentage of the P element in the negative electrode material within the above range, which is beneficial to increase the capacity of the negative electrode material and improve the cycle retention rate of the negative electrode material.

[0039] In some embodiments, the graphite includes at least one of artificial graphite and natural graphite.

[0040] Natural graphite is flake graphite, which is natural crystalline graphite. It is shaped like fish phosphate, belongs to the hexagonal crystal system, has a layered structure, and has good high temperature resistance, electrical conductivity, thermal conductivity, lubrication, plasticity, acid and alkali resistance, etc. Artificial graphite is a graphite material obtained by carbonizing organic matter and then graphitizing it at high temperature.

[0041] In some embodiments, the graphite includes spherical graphite, and the spherical graphite is natural graphite. Specifically, the graded material in the spheroidization process of natural flake graphite can be shaped to obtain spherical graphite. Spherical natural graphite has high isotropy and a close transmission path of lithium ions, which can be beneficial to comprehensively improve the lithium ion transmission efficiency of the negative electrode material.

[0042] In some embodiments, the fixed carbon content of the graphite is ≥ 98%, specifically 98%, 98.5%, 99%, 99.5%, 99.8% or 99.9%, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. Preferably, the mass content of carbon in the graphite is ≥ 99.95%.

[0043] In some embodiments, the average particle size of the primary particles is 1 μm to 5 μm. More specifically, it can be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, etc., but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. Use S-4800 scanning electron microscope to observe the cross-section particles of the negative electrode material, measure the diameter of the primary particles, and take the average value as the average particle size of the primary particles.

[0044] In some embodiments, the angle of repose of the negative electrode material is 30°~50°, specifically 30°, 32°, 34°, 35°, 37°, 40°, 42°, 45°, 48° or 50°, etc., and of course other values ​​within the above range may also be used, which is not limited here. When the angle of repose of the negative electrode material is too large, the friction between the particles of the negative electrode material is too large, which is not conducive to the electrolyte fully infiltrating the negative electrode material, the lithium ion transmission resistance of the negative electrode material increases, the tap density of the negative electrode material decreases, and the fast charging performance also decreases. When the angle of repose of the negative electrode material is too small, although the tap density of the negative electrode material is slightly improved, the compaction density of the negative electrode material decreases, and the energy density also decreases. The present application controls the angle of repose of the negative electrode material within the above range, which can not only promote the electrolyte to fully infiltrate the negative electrode material, improve the specific capacity and fast charging performance of the negative electrode material, but also improve the compaction density of the negative electrode material.

[0045] In some embodiments, the orientation degree OI of the negative electrode material is 1 to 5, specifically 1, 1.5, 2, 2.5, 3, 3.5, 4, 4.5 or 5, etc., and of course other values ​​within the above range. In the present application, when the orientation degree of the negative electrode material is controlled within the above range, the graphite crystal structure can be arranged more orderly, the negative electrode material has a high degree of isotropy, the lithium ion deintercalation rate is closer, the internal resistance of the negative electrode material can be reduced, and the negative electrode material has better cycle performance and rate performance.

[0046] In some embodiments, the median particle size of the negative electrode material is 10 μm to 30 μm, specifically, 10 μm, 11 μm, 12 μm, 14 μm, 15 μm, 16 μm, 20 μm, 25 μm, 28 μm or 30 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0047] In some embodiments, the compaction density of the negative electrode material at 5T pressure is 1.5 g / cm 3 ~1.9 g / cm 3 , specifically 1.5 g / cm 3 , 1.55 g / cm 3 , 1.58g / cm 3 , 1.6g / cm 3 , 1.65g / cm 3 , 1.7g / cm 3 , 1.75g / cm 3 , 1.8 g / cm 3 , 1.85g / cm 3 or 1.9 g / cm 3 Of course, it can also be other values ​​within the above range and is not limited here.

[0048] In some embodiments, the tap density of the negative electrode material is 0.6 g / cm 3 ~1.5g / cm 3 ; Specifically, it can be 0.6g / cm 3 , 0.7g / cm 3 , 0.75g / cm 3 , 0.8g / cm 3 , 0.85g / cm 3 , 0.9g / cm 3 , 0.95g / cm 3 , 1.0g / cm 3 , 1.2g / cm 3 or 1.5g / cm 3 etc., but are not limited to the listed values, and other values ​​not listed within the numerical range are also applicable. Controlling the tap density of the negative electrode material within the above range is conducive to improving the energy density of the lithium-ion battery made of the negative electrode material.

[0049] In some embodiments, the specific surface area of ​​the negative electrode material is 2 m 2 / g~10m 2 / g; specifically, it can be 2.0m 2 / g, 3.0m 2 / g, 4.0m 2 / g, 5.0m 2 / g, 6.0m 2 / g, 7.0m 2 / g, 8.0m 2 / g or 10m 2 / g, etc., and of course, it can also be other numbers within the above range, which is not limited here. The specific surface area of ​​the negative electrode material is controlled within the above range. Controlling the specific surface area of ​​the negative electrode material within the above range is beneficial to improving the cycle performance of the lithium ion battery made of the negative electrode material.

[0050] In some embodiments, the mass content of amorphous carbon in the negative electrode material is 0.1% to 10%, specifically, 0.1%, 0.5%, 1%, 1.5%, 3%, 3.5%, 4%, 6%, 8%, 10%, etc., which is not limited here.

[0051] In a second aspect, the present application provides a method for preparing a negative electrode material, comprising the following steps: S10, gradually adding graphite, a dopant and a high molecular polymer into a mixed solution of water and ethanol, and performing ultrasonic dispersion to obtain a slurry, wherein the sphericity of the graphite is ≥0.8, and the dopant includes at least one of a doped phosphorus source and a doped nitrogen source; S20, drying the slurry by spray drying to obtain a precursor, wherein the spray drying temperature is controlled to be 120° C. to 200° C., and the flow rate of the slurry is 10 mL / min to 50 mL / min; S30, placing the precursor in a rotary kiln, and carbonizing the precursor under a protective atmosphere to obtain a negative electrode material, wherein the carbonization treatment includes a first heating stage, a second heating stage and a third heating stage, the temperature of the first heating stage is 120°C~150°C, the temperature of the second heating stage is 300°C~600°C, and the temperature of the third heating stage is 900°C~1500°C.

[0052] In the preparation method of the negative electrode material provided by the present application, the slurry formed by mixing graphite with a dopant and a high molecular polymer is dried by spray drying. During the spray drying process, by controlling the drying temperature and the flow rate of the slurry, the solvent can evaporate more evenly, and the particle sphericity of the precursor obtained by drying is improved, and the particle bonding becomes less. Then through carbonization treatment, the precursor with higher sphericity is further fully carbonized, mainly because the high molecular polymer in the precursor is fully carbonized to form a carbon material, part of the carbon material connects the graphite primary particles, and part of the carbon material is located on the surface of the secondary particles. The whole carbonization process adopts a stage heating process, which is conducive to improving the particle sphericity of the negative electrode material, so that the isotropy of the negative electrode material particles is improved, which is conducive to maintaining the stability of the secondary particle structure, reducing particle crushing, reducing the aggravation of the side reactions caused by the collapse of the particle structure, and is conducive to improving the cycle performance of the negative electrode material and reducing expansion. Therefore, the negative electrode material prepared in the present application improves the sphericity of the secondary particles of the negative electrode material while doping N element and / or P element, so that the negative electrode material has high specific capacity, excellent cycle stability, and low expansion rate, and can meet the fast charging performance of the negative electrode material.

[0053] The following is a detailed description of the preparation method provided in this scheme: Step S10, gradually adding graphite, dopant and high molecular polymer into a mixed solution of water and ethanol, and ultrasonically dispersing to obtain a slurry, wherein the sphericity of the graphite is ≥0.8, and the dopant includes at least one of a doped phosphorus source and a doped nitrogen source.

[0054] In some embodiments, the graphite includes at least one of artificial graphite and natural graphite.

[0055] Natural flake graphite is natural crystalline graphite, which is similar to fish phosphate, belongs to the hexagonal crystal system, has a layered structure, and has good high temperature resistance, electrical conductivity, thermal conductivity, lubrication, plasticity, acid and alkali resistance, etc. Artificial graphite is a graphite material obtained by carbonizing organic matter and then graphitizing it at high temperature.

[0056] In some embodiments, the graphite includes spherical graphite, and the spherical graphite is natural graphite. Specifically, the graded material in the spheroidization process of natural flake graphite can be shaped to obtain spherical graphite. Spherical natural graphite has high isotropy and a close transmission path of lithium ions, which can be beneficial to comprehensively improve the lithium ion transmission efficiency of the negative electrode material.

[0057] In some embodiments, the median particle size of the graphite is 1 μm to 5 μm, more specifically, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, 3.5 μm, 4 μm, 4.5 μm or 5 μm, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. The median particle size of the graphite is controlled within the above range, which is conducive to taking into account the processing performance, capacity and rate performance.

[0058] In some embodiments, the sphericity of graphite is 0.8-0.9, specifically 0.8, 0.81, 0.82, 0.83, 0.84, 0.85, 0.86, 0.87, 0.88, 0.89, 0.9, etc., which are not limited here. The above sphericity is the particle sphericity corresponding to the cumulative volume distribution percentage reaching 50%. Preferably, the sphericity of the graphite obtained by shaping is 0.85-0.9. The higher the sphericity, the lower the orientation of the graphite. During the cycle of the negative electrode material, the expansion stress generated by the continuous embedding and extraction of lithium ions between the graphite layers can be released in multiple directions, reducing the particle breakage caused by excessive local expansion stress of the negative electrode material particles, improving the expansion effect of the negative electrode material, and effectively improving the cycle performance of the negative electrode material.

[0059] In some embodiments, the graphite may also be artificial graphite.

[0060] In some embodiments, the mass content of carbon in the graphite is ≥ 99.5%.

[0061] In some embodiments, the doping phosphorus source includes at least one of ammonium polyphosphate, phosphoric acid, ammonium dihydrogen phosphate, and diamine hydrogen phosphate.

[0062] In some embodiments, the doping nitrogen source includes at least one of melamine, urea, and carbon nitride (C3N4).

[0063] In some embodiments, the high molecular weight polymer includes at least one of polyvinylpyrrolidone, polyacrylamide, polyvinyl alcohol, and hydroxymethyl cellulose.

[0064] In some embodiments, the mass ratio of the high molecular polymer to graphite is 100:(200-400), specifically 100:200, 100:220, 100:250, 100:300, 100:320, 100:350, 100:380 or 100:400, etc., which is not limited here.

[0065] In some embodiments, the mass ratio of the doped phosphorus source, the doped nitrogen source and the graphite is (1-10): (1-10): 100, and specifically can be 1:1:100, 1:2:100, 1:5:100, 2:5:100, 2:10:100, 3:5:100, 5:5:100 or 10:10:100, etc., and is not limited here.

[0066] In some embodiments, the volume ratio of graphite to solvent is 100:(100:400), and can specifically be 100:100, 100:150, 100:200, 100:250, 100:300, 100:350 or 100:400, etc., and of course can also be other values ​​within the above range, which is not limited here.

[0067] In some embodiments, the solvent includes water and ethanol, and the volume ratio of water to ethanol can be 9:1 to 10:1, which is not limited herein.

[0068] In some embodiments, the frequency of ultrasonic dispersion is 20 kHz-100 kHz, and specifically may be 20 kHz, 40 kHz, 50 kHz, 70 kHz, 80 kHz, 90 kHz or 100 kHz, etc., which is not limited here.

[0069] In some embodiments, the ultrasonic dispersion time is 6 h to 24 h, specifically, it can be 6 h, 8 h, 10 h, 12 h, 15 h, 18 h, 20 h or 24 h, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0070] S20, drying the slurry by spray drying to obtain a precursor.

[0071] In some embodiments, the spray drying temperature is 120°C to 200°C, specifically, it can be 120°C, 130°C, 140°C, 150°C, 160°C, 180°C or 200°C, etc., but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable. When the spray drying temperature is too low, the precursor formed by the droplets that cannot be dried in time is easy to stick to each other into blocks, resulting in a decrease in the sphericity of the precursor. When the spray drying temperature is too high, the solvent in the droplets evaporates too quickly, the bonding stability between the primary graphite particles decreases, and it is not easy to agglomerate to form precursor secondary particles, and the sphericity of the secondary particles will also decrease. The present application controls the temperature of spray drying within the above range, which is conducive to improving the sphericity of the precursor particles and improving the structural stability of the precursor particles.

[0072] In some embodiments, the flow rate of the slurry is 10 mL / min~50mL / min, specifically 10 mL / min, 15mL / min, 20mL / min, 25mL / min, 30mL / min, 35mL / min or 50mL / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are equally applicable. When the flow rate of the slurry is too low, the number of graphite primary particles is too small, and it is not easy to agglomerate to form precursor secondary particles, and the sphericity of the secondary particles decreases. When the flow rate of the slurry is too fast, too many graphite primary particles are easily bonded into blocks, resulting in excessive particle size of the precursor secondary particles, and the sphericity will also decrease. The present application controls the flow rate of the slurry within the above range, and the particle size of the precursor particles can be adjusted within a suitable range, which is conducive to improving the sphericity of the precursor particles.

[0073] S30, placing the precursor in a rotary kiln, and carbonizing the precursor under a protective atmosphere to obtain a negative electrode material, wherein the carbonization treatment includes a first heating stage, a second heating stage and a third heating stage, the temperature of the first heating stage is 120°C~150°C, the temperature of the second heating stage is 300°C~600°C, and the temperature of the third heating stage is 900°C~1500°C.

[0074] In some embodiments, the rotation speed of the rotary kiln is 5 rpm to 20 rpm, specifically 5 rpm, 8 rpm, 10 rpm, 12 rpm, 15 rpm, 18 rpm or 20 rpm, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. By controlling the rotation speed of the rotary kiln, the roundness of the secondary particles obtained by granulation can be maintained.

[0075] In some embodiments, the carbonization treatment includes a first heating stage, a second heating stage and a third heating stage, the temperature of the first heating stage is 120°C~150°C, the temperature of the second heating stage is 300°C~600°C, and the temperature of the third heating stage is 900°C~1500°C.

[0076] In some embodiments, the temperature of the first heating stage is 120°C to 150°C, specifically, 120°C, 130°C, 140°C or 150°C, etc., but is not limited to the listed values, and other values ​​not listed within the numerical range are also applicable. It can be understood that at this temperature, a small amount of solvent remaining in the material during the spray drying process can be deeply dried to reduce the impact on the material structure during the subsequent carbonization process.

[0077] In some embodiments, the heating rate of the first heating stage is 5° C. / min.

[0078] In some embodiments, the temperature of the second heating stage is 300°C to 600°C, specifically, 300°C, 330°C, 350°C, 380°C, 400°C, 450°C, 400°C, 450°C, 500°C, 550°C or 600°C, etc., but is not limited to the listed values, and other values ​​not listed in the numerical range are also applicable. It can be understood that the binder has a significant weight loss in this temperature range. Keeping the temperature under this temperature condition for a period of time allows some small molecules to be fully released at this temperature, avoiding damage to the surface of the material in the high temperature stage, so that the material forms a more dense secondary particle structure after carbonization.

[0079] In some embodiments, the insulation time of the second heating stage is 2h~4h, specifically, it can be 2h, 2.5h, 3h, 3.5h or 4h, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0080] In some embodiments, the heating rate of the second heating stage is 0.5°C / min~2°C / min, specifically 0.5°C / min, 1°C / min, 1.2°C / min, 1.5°C / min, 1.8°C / min or 2°C / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0081] In some embodiments, the temperature of the third heating stage is 900°C~1500°C, specifically, it can be 900°C, 1000°C, 1050°C, 1100°C, 1200°C, 1300°C, 1400°C or 1500°C, but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0082] In some embodiments, the insulation time of the second heating stage is 2h~10h, specifically, it can be 2h, 3h, 4h, 5h, 6h, 7h, 8h or 10h, etc., but it is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0083] In some embodiments, the heating rate of the second heating stage is 2.5°C / min~10°C / min, specifically 2.5°C / min, 3°C / min, 5°C / min, 6°C / min, 8°C / min or 10°C / min, etc., but is not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0084] In some embodiments, the protective atmosphere includes at least one of high purity nitrogen, helium, argon, neon, krypton, and xenon.

[0085] In some embodiments, the gas flow rate of the protective atmosphere is 0.1 mL / s to 10 mL / s, specifically 0.1 mL / s, 1 mL / s, 2 mL / s, 3 mL / s, 5 mL / s, 6 mL / s, 8 mL / s or 10 mL / s, etc., which is not limited here.

[0086] In the present application, by controlling the rotation speed, carbonization temperature, time and other parameters of the rotary kiln, the secondary particles can be reconstructed in the rotary kiln, the surface defects of the secondary particles can be reduced, the sphericity of the secondary particles can be improved, and the surface of the secondary particles can have a stable solid-liquid reaction interface, thereby improving the cycle performance of the negative electrode material.

[0087] In some embodiments, after the carbonization treatment, at least one of screening and demagnetization is performed.

[0088] In some embodiments, the screening method is any one of a fixed screen, a drum screen, a resonance screen, a roller screen, a vibrating screen and a chain screen.

[0089] In some embodiments, the demagnetization equipment is any one of a permanent magnetic drum magnetic separator, an electromagnetic iron remover and a pulsating high gradient magnetic separator. The purpose of demagnetization is to control the magnetic substance content of the negative electrode material, avoid the magnetic substance affecting the charging and discharging of the lithium-ion battery, and ensure the safety of the battery during use.

[0090] In a third aspect, an embodiment of the present invention further provides a battery, Figure 1 A schematic diagram of the discharge state of a battery provided in an embodiment of the present application, such as Figure 1 As shown, the battery includes a housing and an electrode assembly, and the electrode assembly includes a positive electrode sheet 1, a negative electrode sheet 2 and a separator 3, and the separator 3 is arranged between the positive electrode sheet 1 and the negative electrode sheet 2. The electrode assembly can be a laminated structure, which is formed by alternately stacking the positive electrode sheet 1, the separator 3 and the negative electrode sheet 2. In other embodiments, the electrode assembly can also be a winding structure, which is formed by stacking the positive electrode sheet, the separator and the negative electrode sheet in sequence and then winding them.

[0091] In some embodiments, the positive electrode sheet 1 includes a positive electrode current collector 101 and a positive electrode active layer 102 disposed on at least one surface of the positive electrode current collector 101 .

[0092] In some embodiments, the positive electrode current collector 101 may be aluminum foil or nickel foil, or any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil (aluminum foil or nickel foil, etc.) and a polymer substrate. The positive electrode active layer 102 includes a positive electrode active material, which includes a compound that can reversibly embed and de-embed metal ions.

[0093] In some embodiments, the positive electrode active material may include a lithium transition metal composite oxide, a sodium transition metal composite oxide, etc. The lithium transition metal composite oxide contains lithium and at least one element selected from cobalt, manganese, and nickel.

[0094] In some embodiments, the positive electrode active material may include but is not limited to lithium cobalt oxide (LiCoO 2 ), lithium nickel manganese cobalt ternary materials (NCM), lithium manganese oxide (LiMn 2 O 4 ), lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O 4 ) or lithium iron phosphate (LiFePO 4 ) at least one of.

[0095] In some embodiments, the negative electrode sheet 2 includes a negative electrode current collector 201 and a negative electrode active material layer 202 disposed on at least one surface of the negative electrode current collector.

[0096] In some embodiments, the negative electrode current collector 201 may use at least one of copper foil, nickel foil, stainless steel foil, titanium foil or carbon-based current collector, etc., or may be any composite current collector disclosed in the prior art, such as but not limited to the current collector formed by combining the aforementioned conductive foil and polymer substrate. The negative electrode active material layer 202 includes a negative electrode material, which is the negative electrode material of the first aspect described above or the negative electrode material prepared by the above preparation method.

[0097] The battery provided in the embodiment of the present application has the advantages of high capacity, high initial efficiency, long cycle life, excellent rate performance and low expansion. The battery can be a lithium ion battery, a sodium ion battery, a solid electrolyte battery, etc., which is not limited here.

[0098] The embodiments of the present invention are further described below with reference to a plurality of embodiments.

[0099] The embodiments in this patent are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention; it should be noted that, unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by technicians in the technical field of this application; in the absence of conflict, the embodiments of this application and the features in the embodiments can be combined with each other; in the following description, many specific details are explained to facilitate a full understanding of this application, and the described embodiments are only part of the embodiments of this application, not all of the embodiments. The embodiments of this application are further explained in multiple embodiments below.

[0100] Embodiment 1: The method for preparing the negative electrode material comprises the following steps: (1) 2 parts of melamine, 2 parts of ammonium polyphosphate, 20 parts of polyvinyl pyrrolidone and 100 parts of graphite primary particles were gradually added to a mixed solution consisting of 200 parts of water and 20 parts of ethanol, and then ultrasonically dispersed at a frequency of 60 kHz for 10 hours to obtain a slurry.

[0101] (2) The slurry is dried by spray drying at a temperature of 180° C. to obtain a precursor.

[0102] (3) The precursor was placed in a rotary kiln for carbonization treatment, and 5 mL / s of nitrogen was introduced. The temperature program of the carbonization treatment was as follows: heating to 120°C at 5°C / min and keeping it warm for 1 h, then heating to 450°C at 1°C / min and keeping it warm for 2 h, and finally heating to 1100°C at 5°C / min and keeping it warm for 3 h. After natural cooling, the negative electrode material was obtained.

[0103] The negative electrode material prepared in Example 1 of the present application includes secondary particles, wherein the secondary particles include primary particles and amorphous carbon connecting the primary particles, and the primary particles include graphite. Figure 2 This is a graph showing the sphericity test data of the negative electrode material prepared in Example 1 of the present application, as shown in FIG. Figure 2 As shown, S 10 =0.77, S 50 =0.89, S 90 =0.95. According to the preparation process of Example 1, relevant parameters were adjusted to prepare Examples 2 to 18 (abbreviated as S1 to S18) and Comparative Examples 1 to 4 (D1 to D4), and the specific parameter changes are shown in Table 1: Table 1. Preparation process parameters of negative electrode materials

[0104] Test Method (1) Test method for doping elements and their content in negative electrode materials: The elemental analysis was carried out using an X-ray photoelectron spectrometer (XPS, model: Thermo ESCALAB 250XI).

[0105] (2) Test method for particle size distribution of negative electrode materials: The particle size test method refers to GB / T 19077-2016. The particle size distribution range of the negative electrode material was tested by the Mastersizer 3000 laser particle size analyzer of Malvern Instruments Ltd., UK. The volume-based cumulative particle size distribution of the particle size distribution was measured by laser diffraction method. D50 represents the particle size corresponding to the cumulative volume distribution percentage reaching 50%.

[0106] (3) Test method for the tap density of negative electrode materials: Use a Microbe Tap Density Tester to test the specific surface area of ​​the material. Place the negative electrode material in the sample chamber of the tap density tester, vibrate it 1000 times, and record the sample volume at this time. The tap density can be calculated according to the mass-to-volume ratio.

[0107] (4) Test method for compaction density of negative electrode materials: The compaction density test was carried out using the national standard GB / T 24533-2009 test method for lithium-ion battery graphite negative electrode materials, with a test pressure of 5 tons.

[0108] (5) Testing method for specific surface area of ​​negative electrode material: Under constant temperature and low temperature, after measuring the adsorption amount of gas on the surface of the negative electrode material at different relative pressures, the monolayer adsorption amount of the sample is obtained based on the Brownauer-Etter-Taylor adsorption theory and its formula (BET formula), thereby calculating the specific surface area of ​​the material.

[0109] (6) Test of repose angle of negative electrode material: Slowly add the negative electrode material from the top of the funnel, and then measure the inclination angle of the negative electrode material leaking out from the bottom of the funnel to form a cone-shaped accumulation on the horizontal plane, which is the angle of repose (angle of repose tester, model SPT-105).

[0110] (7) Test of orientation of negative electrode materials: The ratio of the peak area C004 of the (004) plane to the peak area C110 of the (110) plane of the negative electrode material particles was determined by X-ray diffraction pattern using the PANalytical X'pert PRO X-ray diffractometer of the Netherlands and referring to the method in GB / T 24533-2019 "Graphite Anode Materials for Lithium-ion Batteries".

[0111] (8) Sphericity test of the negative electrode material: The sphericity of the negative electrode material was tested and analyzed using the QICPIC dynamic particle imaging spectrometer from Sympatec of Germany.

[0112] (9) Sphericity index test of the negative electrode material: 5g of negative electrode material was added to a solution of 45mL water and 5mL ethanol, and then placed in an ultrasonic cell crusher at a frequency of 20kHz. After dispersion for 10min, the sphericity test was performed. The sphericity of the particles corresponding to the cumulative volume distribution percentage of the negative electrode material reaching 50% was S 50’ , sphericity index R = S 50 / S 50’ .

[0113] (10) Electrochemical performance test method: Half-cell test: The negative electrode materials prepared in the embodiment and the comparative example were dispersed in N-methylpyrrolidone at a mass ratio of 92:5:3, conductive carbon black and polyvinylidene fluoride to obtain a negative electrode slurry. The negative electrode slurry was evenly coated on a copper foil current collector and dried in a vacuum oven at 120°C to obtain a negative electrode sheet. A metal lithium sheet was used as a counter electrode, the separator was celgard C2400, and the electrolyte was 1.3M LiPF 6 The electrolyte solution contains ethylene carbonate (EC), polycarbonate (PC) and diethyl carbonate (DEC) in a volume ratio of 3:1:6. The button cell was assembled in an argon-filled glove box. The charge and discharge test was performed at a current density of 0.1C and a charge and discharge interval of 0.01-1.5V. The first cycle reversible capacity was obtained by cyclic charge and discharge.

[0114] Full battery test: The negative electrode materials prepared in the examples and comparative examples were used as positive electrodes with large single crystal nickel cobalt manganese oxide (NCM523) and 1 mol / L LiPF electrolyte. 6 The electrolyte contains a solvent of ethylene carbonate (EC), polycarbonate (PC), diethyl carbonate (DEC) and ethyl methyl carbonate (EMC) solution in a volume ratio of 1:0.3:1:1. The separator is a PP / PE / PP three-layer separator with a thickness of 16μm. It is made into a soft-pack battery of about 3Ah to test the full battery performance of the material.

[0115] Table 2. Performance comparison results of negative electrode materials

[0116] According to the test data in Table 1 and Table 2, Examples 1 to 9 mainly explore the effects of doped phosphorus sources and doped nitrogen sources on negative electrode materials. According to the negative electrode materials prepared in Examples 1 to 4, during the preparation process, as the amount of doped phosphorus source added increases, the mass percentage of the P element in the negative electrode material also increases. Similarly, for the negative electrode materials of Examples 1 and 5 to 7, as the amount of doped nitrogen source added increases, the mass percentage of the N element in the negative electrode material also increases. According to the test data of Examples 8 to 9, different types of doped phosphorus sources or doped nitrogen sources can effectively increase the mass percentage of the doped elements in the negative electrode material.

[0117] Table 3. Sphericity parameters of negative electrode materials

[0118] According to the data in Table 1, Table 2 and Table 3, Examples 1 and Examples 11 to 16 mainly explore the effects of process parameters such as spray drying temperature, slurry flow rate, solvent ratio and ultrasonic dispersion on the sphericity of the negative electrode material.

[0119] According to the test data of Example 1 and Examples 11-12, as the volume proportion of the solvent in the slurry increases, the sphericity index P of the negative electrode material slowly increases. This may be because the volume proportion of the solvent in the slurry increases, and the dispersion uniformity of components such as graphite primary particles and high molecular polymers is improved. Therefore, the sphericity of secondary particles formed by the agglomeration of primary particles is also improved.

[0120] According to the test data of Examples 1 and 13-14, the spray drying temperature of Example 13 is increased, and the corresponding particle sphericity is S when the cumulative volume distribution percentage reaches 10%. 10 The sphericity of the secondary particles with relatively small particle size decreased slightly. This may be because after the drying temperature is increased, the solvent in the droplets evaporates faster, the bonding stability between some graphite primary particles decreases, and the sphericity of the secondary particles formed by agglomeration decreases slightly. The spray drying temperature of Example 14 is reduced, and the particle sphericity is S 10 , S 50 , S 90 This may be because after the drying temperature is lowered, the droplets cannot be dried in time, and the formed precursors are easy to stick to each other into blocks, resulting in a slight decrease in the sphericity of the precursor.

[0121] According to the test data of Examples 1 and 15-16, the droplet flow rate of Example 13 decreased during the spray drying process, which may be because the number of primary graphite particles in the droplets was too small and it was not easy to agglomerate to form precursor secondary particles. The particle sphericity of the secondary particles was S 10 , S 50 , S 90 Compared with Example 1, they are slightly decreased. In Example 16, the droplet flow rate increased during the spray drying process, which may be because too many primary graphite particles are easily agglomerated, resulting in the particle size of the precursor secondary particles being too large, and the particle sphericity of the secondary particles is S 10 , S 50 , S 90 Compared with Example 1, they are slightly decreased.

[0122] According to the test data of Examples 1 and 17-18, Example 17 is doped with only P element, and Example 18 is doped with only N element, but the sphericity S of the secondary particles is 10 , S 50 , S 90 Similar to Example 1.

[0123] In the spray drying process of Comparative Example 2, the drying temperature was too low. In Comparative Example 3, the spray drying process of the present application was not adopted, but vacuum drying was adopted. In Comparative Example 4, the droplet flow rate was too large during the spray drying process, and the particle sphericity of the negative electrode material could not meet 0.75≤S 10 ≤0.85, 0.85≤S 50 ≤0.9, 0.9≤S 90 ≤1.0.

[0124] The negative electrode materials prepared in the above examples and comparative examples were prepared into button-type batteries, and the measured electrochemical properties are shown in Table 4.

[0125] Table 4. Battery performance comparison table

[0126] According to the test data of Examples 1 to 18, the negative electrode material prepared in the examples can be doped with N element and / or P element to increase the specific capacity of the negative electrode material. 10 ≤0.85, 0.85≤S 50 ≤0.9, 0.9≤S 90 ≤1.0, the secondary particles have a high degree of isotropy, and during the cycle, the secondary particles shrink and expand radially. Due to the high degree of isotropy, the expansion stress can be effectively released, which is conducive to maintaining the stability of the secondary particle structure, reducing particle breakage, and reducing the aggravation of side reactions caused by particle structure collapse, which is conducive to improving the cycle capacity retention rate of the negative electrode material; and due to the high sphericity of the secondary particles, the lithium ion deintercalation rate is closer, which can reduce the internal resistance of the negative electrode material, and the negative electrode material has better fast charge rate performance. The negative electrode material can have excellent specific capacity, excellent cycle stability, and low expansion rate, which can meet the fast charge performance of the negative electrode material.

[0127] Compared with Example 1, the negative electrode material prepared in Comparative Example 1 is not doped with N element and / or P element, the active lithium storage sites of the negative electrode material are reduced, and the specific capacity of the negative electrode material is significantly reduced compared with Example 1. The negative electrode material prepared in Comparative Example 2 is not doped with N element and / or P element, and the negative electrode material cannot meet 0.75≤S 10 ≤0.85, 0.85≤S 50 ≤0.9, 0.9≤S 90 ≤1.0, the specific capacity of the negative electrode material is greatly reduced, and the cycle capacity retention rate under fast charging is significantly reduced, which cannot meet the fast charging requirements.

[0128] Compared with Example 1, the negative electrode materials prepared in Comparative Examples 3 and 4 have similar specific capacities, but the negative electrode materials cannot satisfy the condition of 0.75≤S 10≤0.85, 0.85≤S 50 ≤0.9, 0.9≤S 90 ≤1.0, the isotropy of the negative electrode material particles decreases, the lithium ion deintercalation rates become uneven, the lithium ion transmission efficiency decreases, the rate performance of the negative electrode material decreases, and the cycle capacity retention rate of the negative electrode material also decreases significantly.

[0129] Although the present application is disclosed as above with preferred embodiments, it is not intended to limit the claims. Any technical personnel in this field may make several possible changes and modifications without departing from the concept of the present application. Therefore, the scope of protection of the present application shall be based on the scope defined by the claims of the present application.

Claims

1. A negative electrode material, characterized in that: The negative electrode material includes secondary particles, the secondary particles include primary particles and amorphous carbon connecting the primary particles, the primary particles include graphite; the negative electrode material includes at least one of N element and P element; In the negative electrode material, when the cumulative volume distribution percentage reaches 10%, the corresponding particle sphericity is S 10 When the cumulative volume distribution percentage reaches 50%, the corresponding particle sphericity is S 50 When the cumulative volume distribution percentage reaches 90%, the corresponding particle sphericity is S 90 , 0.75≤S 10 ≤0.85, 0.85≤S 50 ≤0.9, 0.9≤S 90 ≤1.

0.

2. The negative electrode material according to claim 1, characterized in that The sphericity index of the negative electrode material is R≥1.05, R=S 50 / S 50’ , wherein 2g of negative electrode material was dispersed in a mixed solution of 45mL of water and 5mL of ethanol, and after ultrasonic crushing at a frequency of 20kHz for 10min, the particle sphericity corresponding to the cumulative volume distribution percentage of the negative electrode material reaching 50% was S 50’ .

3. The negative electrode material according to claim 1, characterized in that The mass percentage of N element in the negative electrode material is 0.5% to 2%.

4. The negative electrode material according to claim 1, characterized in that The mass percentage of P element in the negative electrode material is 0.05% to 0.5%.

5. The negative electrode material according to claim 1, characterized in that The negative electrode material meets at least one of the following characteristics: (1) The graphite includes at least one of artificial graphite and natural graphite; (2) The graphite includes spherical natural graphite; (3) The average particle size of the primary particles is 1 μm to 5 μm.

6. The negative electrode material according to claim 1, characterized in that The repose angle of the negative electrode material is 30° to 50°.

7. The negative electrode material according to claim 1, characterized in that The orientation degree OI of the negative electrode material is 1~5.

8. The negative electrode material according to claim 1, characterized in that The negative electrode material meets at least one of the following characteristics: (1) The compaction density of the negative electrode material under a pressure of 5T is 1.5 g / cm 3 ~1.9 g / cm 3 ; (2) The tap density of the negative electrode material is 0.5 g / cm 3 ~0.9g / cm 3 ; (3) The specific surface area of ​​the negative electrode material is 2 m 2 / g~10 m 2 / g.

9. The negative electrode material according to claim 1, characterized in that The median particle size of the negative electrode material is 10 μm to 30 μm.

10. A battery, characterized in that: The battery comprises the negative electrode material according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Graphite secondary particle, and lithium secondary battery comprising same

    CN105794027A

  • Negative active material, negative pole piece and secondary battery

    CN118538914A

  • Spherical graphite material and preparation method thereof, negative plate and battery

    CN119050347A

  • Method for producing a battery active material and product thereof

    WO2024040048A1

Cited By

  • Negative electrode material, negative electrode sheet, and secondary battery

    WO2026011870A1